Agriculture for development in Ghana: New opportunities and challenges - Breisinger, Clemens; Diao, Xinshen; Thurlow, James; Al-Hassan, Ramatu M. (International Food Policy Research Institute, 2008)
This paper has been prepared in support of the Comprehensive Africa Agriculture Development Program (CAADP) roundtable in Ghana. The study also takes a fresh perspective on the role of agriculture for development in light of the global food crisis. It addresses two main questions: what are the impacts of Green-revolution type agricultural growth to reach the CAADP goal in Ghana? Given the large investments required to achieve such productivity-led growth, what is the sector's contribution to the overall economy? Results from the dynamic computable general equilibrium model suggest that by closing the existing yield gaps in crop production and supporting essential growth in the livestock sector Ghana can achieve CAADP's 6 percent growth target. In this process, agriculture supports the rest of the economy through substantial and largely invisible monetary transfers to the nonagricultural sectors, which are primarily driven by the reduction of domestic food prices. Thus, CAADP growth benefits both rural and urban households, and reduces poverty by more than half within 10 years. However, widening regional disparities between the North and the rest of Ghana will increasingly pose a challenge for the development. Additional measures more targeted towards generating growth in the lagging North will be necessary to bridge the income gap and reach Ghana's poorest of the poor.